2020
DOI: 10.1186/s12885-020-06732-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of individual background on the unmet needs of cancer survivors and caregivers – a mixed-methods analysis

Abstract: Background Cancer survivors and their caregivers may have various unmet needs that are medically difficult to solve. Previous studies have suggested the relations between individuals’ backgrounds and their unmet needs. We conducted a large-scale analysis to clarify the influence of individuals’ backgrounds, primarily cancer type, on specific types of unmet needs. Methods Using a mixed-methods approach, we analyzed records of first-time callers to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…44 Furthermore, young cancer survivors have fewer individual experiences compared with older cancer survivors, and therefore the adaptation process of this group might be more difficult than for the older group. Previous research reported that individual backgrounds and present symptoms play a more important role in unmet needs than age per se, 45 while younger cancer survivors consistently report higher unmet needs than other age group. 46 Furthermore, female cancer survivors reported higher unmet needs scores than their male counterparts, possibly because female cancer survivors had more points of concern such as issues relating to body image and residual symptoms (which, in turn, are associated with breast cancer, as discussed below, which generally affects women), and personal relationships, etc.…”
Section: Discussionmentioning
confidence: 96%
“…44 Furthermore, young cancer survivors have fewer individual experiences compared with older cancer survivors, and therefore the adaptation process of this group might be more difficult than for the older group. Previous research reported that individual backgrounds and present symptoms play a more important role in unmet needs than age per se, 45 while younger cancer survivors consistently report higher unmet needs than other age group. 46 Furthermore, female cancer survivors reported higher unmet needs scores than their male counterparts, possibly because female cancer survivors had more points of concern such as issues relating to body image and residual symptoms (which, in turn, are associated with breast cancer, as discussed below, which generally affects women), and personal relationships, etc.…”
Section: Discussionmentioning
confidence: 96%
“… 22 Terms related to CRC treatment, tests, and diseases were also highly ranked, similar to research showing a high need for treatment-related resources, treatment, unmet needs related to the cancer itself, and information. 3 , 31 Notably, there were some differences between caregivers and patients, with terms related to defecation and pain appearing in the higher ranks for patients. Such symptoms have significant implications for patients regarding the fear of recurrence and functional loss.…”
Section: Discussionmentioning
confidence: 99%
“…Individual survivors have varying levels and types of needs and personalised approaches to care are required. A recent analysis found that individuals' background and presence of symptoms play a more important role in the profile of unmet needs than cancer type (Watanabe et al, 2020 ). Our study findings differ from those of others in some respects but inconsistencies in evidence about unmet needs have been widely reported (Puts et al, 2012 ; Willems et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%